Achieving Residential Connectivity and Density Goals with Computer-Generated Plans in a Greenfield Area. (June 2014) - Sun, Yuchao; Qiu, Min; Taplin, John
An algorithm has been developed to generate, without external intervention, a road and land-use plan for a regular or irregular site. It starts from an 'embryo' and grows a plan rather than trying to modify an initial solution. The basic modules are universal building blocks which change and adapt in a guided search with random selection of branching points followed by operations to add links or make connections. Deletion operators guide development by removing branches which do not improve the outcome. A hypothetical application, maximizing combined everyone-to-everyone connectivity and dwelling density, has evolved a highly interconnected street plan. However, no step is specific to the example; the operators will grow a road and land-use network under various specifications and constraints guided by an objective function. Making the process applicable to an actual development might require more constraints and certainly an enlarged objective function. Cost and other goals can be included so long as each goal is functionally related in some way to every change in the plan made by the search procedure.